The peculiarities of usage of metaphors in political diskurse of modern social and political journalism (based on Ukrainian and Czech periodicals) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the annotated article the author makes an attempt to compare metaphors in political diskurse from the point of the peculiarities of its usage in modern Ukrainian and Czech social and political journalism.
Keywords: metaphor; political metaphor; social and political journalism; publicistic metaphor